Xiamix a knowledge and Social-Cohesive city for the developing world - Yunda Lozano, Juan Guillermo (el autor, 2009)
Xiamen, a city in the south eastern coast of China, is experiencing and accelerated urbanization. Unfortunately, recent urban improvements are being done on behalf of the displacement of traditional population and clearances of the old urban fabric. In frame of a rapid economic growth is important to ask if the new Chinese city addresses the specific problematic of the site and the future trends of economy. Through an analysis of the current urbanization in Xiamen, this work pretends to find new alternatives of urban development; taking into account, the country's challenges in the fields of innovation, knowledge economy and social-cohesion. A spatial proposal for a redevelopment in the city will be formulated, aiming to trace alternatives of urban renewal that could be implemented not only in China but also in other Developing Countries.